Impact of expert pathologic review of thymic epithelial tumours on diagnosis and management in a real-life setting: A RYTHMIC study. (January 2021) - Molina, Thierry J.; Bluthgen, Maria V.; Chalabreysse, Lara; de Montpréville, Vincent T.; de Muret, Anne; Dubois, Romain; Hofman, Véronique; Lantuejoul, Sylvie; le Naoures, Cécile; Mansuet-Lupo, Audrey; Parrens, Marie; Piton, Nicolas; et al.
Abstract: Background: Classification of thymic epithelial tumours (TETs) is known to be challenging; however, the level of discordances at a nationwide level between initial and expert diagnosis and their clinical consequences are currently unknown. RYTHMIC is a national network dedicated to the management of TET based on initial histological diagnosis, followed by an additional expert review of all cases. Our aim was to evaluate the discordances between initial and expert diagnoses and whether they would have led to different clinical management. Patients and methods: We conducted a retrospective analysis of the cohort of patients discussed at RYTHMIC tumour board from January 2012 to December 2016. Assessment of disagreement was made for histological typing and for staging. The discordances were classified as major or minor based on whether they would have changed or not the proposed therapeutic strategy, respectively. Follow-up of the patients with major discordances was conducted until December 2018. Results: Four hundred sixty-seven patients were reviewed, and 183 (39%) discordances were identified either related to histological subtype (132) and/or stage (72). Major discordances were identified in 27 patients (6%). They included 16 patients with TET for whom treatment recommendation based on the central review would have been post-operative radiotherapy, whereas it had not been the case. However, follow-up did not show any progression among the 15 patients with high-grade histology and/or stage resected thymomas. On the other hand, among the remaining 11 patients including 7 with a diagnosis other than TET, the overall management or follow-up would have been completely different with the expert diagnosis. Conclusion: Our real-life cohort reveals a high level of discordances considering TET diagnosis and supports expert review for optimal clinical management. Highlights: We analysed the impact of expert pathologic review of thymic epithelial tumours (TETs) in a nationwide network. A cohort of 467 patients with TET was studied in a real-life setting. We identified an overall discordance rate of 39% considering histotype and/or stage. Change for post-operative radiotherapy or disease management involved 6% of patients. Expert pathologic review of TET contributes to a better treatment decision-making.